2015
DOI: 10.1038/srep15864
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Ursolic acid exerts anti-cancer activity by suppressing vaccinia-related kinase 1-mediated damage repair in lung cancer cells

Abstract: Many mitotic kinases have been targeted for the development of anti-cancer drugs, and inhibitors of these kinases have been expected to perform well for cancer therapy. Efforts focused on selecting good targets and finding specific drugs to target are especially needed, largely due to the increased frequency of anti-cancer drugs used in the treatment of lung cancer. Vaccinia-related kinase 1 (VRK1) is a master regulator in lung adenocarcinoma and is considered a key molecule in the adaptive pathway, which main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In our earlier studies, we have identified UA as an antiaging phytochemical, with enhanced health parameters in C. elegans (4). UA has also proved to have broadspectrum antitumor effects tested in various cancer models (5)(6)(7), with a lead in preclinical and clinical studies where liposomal ursolic acid was used to determine the toxicity and pharmacokinetics in healthy adult human volunteers and in patients with advanced solid tumors (8,9). Moreover, a unified model integrating cancer to aging has been documented in several studies (10,11).…”
mentioning
confidence: 99%
“…In our earlier studies, we have identified UA as an antiaging phytochemical, with enhanced health parameters in C. elegans (4). UA has also proved to have broadspectrum antitumor effects tested in various cancer models (5)(6)(7), with a lead in preclinical and clinical studies where liposomal ursolic acid was used to determine the toxicity and pharmacokinetics in healthy adult human volunteers and in patients with advanced solid tumors (8,9). Moreover, a unified model integrating cancer to aging has been documented in several studies (10,11).…”
mentioning
confidence: 99%